Los juegos cognitivos en el desarrollo del pensamiento lógico matemático de niños y niñas de inicial II de 3-4 años de edad en la Unidad Educativa Verbo Divino de la ciudad Guaranda provincia de Bolívar en el periodo 2024. - Freire Cando, Alexandra Estefanía (2024)
The present research project, entitled "Los juegos cognitivos en el desarrollo del pensamiento lógico-matemático de niños y niñas de Inicial II de 3 a 4 años de edad en la Unidad Educativa Verbo Divino de la ciudad de Guaranda, provincia de Bolívar, en el periodo 2024", had as its general objective to establish the influence of cognitive games in the development of logical-mathematical thinking, thus improving the teaching-learning processes in this age group. The research was based on a mixed approach, combining qualitative and quantitative methods, and was developed under an exploratory, descriptive and explanatory design. These approaches allowed key information to be collected through techniques such as the structured survey and the direct observation form, applied to a population made up of 4 teachers from Initial II and 32 students. Throughout the study, various activities were implemented that contributed to the strengthening of mathematical, cognitive and critical thinking skills in children. These activities were designed to assess and enhance logical- mathematical development, ensuring meaningful learning. The various activities were used to develop a teaching guide for cognitive games, which proposes fun and playful strategies to encourage logical- mathematical development in the classroom. This tool seeks to become a valuable resource for teachers, promoting dynamic and effective learning, in accordance with the needs and characteristics of the initial level. Cognitive games represent an effective methodology to stimulate the comprehensive development of children, enhancing their mathematical skills and critical thinking